PENGARUH PENDIDIKAN KESEHATAN DENGAN PENERAPAN METODE BERNYANYI TERHADAP KEMAMPUAN MENCUCI TANGAN PADA SISWA KELAS A1 DI RA MUSLIMAT DARUL FAIZIN I DESA CATAK GAYAM MOJOWARNO JOMBANG - Titiek Idayanti; Henny Vidya; Surya Mustikasari (LPPM Politeknik Kesehatan Kerta Cendekia, 2017)
Health education hearts washing hands a Primary Health Need implanted on Childhood. Lack of ability to washing hands because of Child Special Methods Appropriate for preschoolers. For overcoming the lack of ability to get washing hands Keep Singing Method Hand wash for improve the Good and True. The design of this study quasy experiment desaign pre-post test. Sampling methods How non propability with the ways total sampling. Samples were taken by 30 respondents comprised 15 treatment group and control group 15 on the Childhood Preschool Grade A1 RA's Women Darul Faizin I In the village Catak Gayam Mojowarno Jombang on February 2017. Observation Data Research using sheet. Taxable income tabulated data analyzed using Mann Whitney and Wilcoxon Rank Test of significance with rate of 0.05. Results of statistical data showing the ability of After washing hands done Singing Method treatment group and control group washing hands ρ = 0,000 <α = 0.05 So Hₒ rejected H1 accepted And That means no difference between treatment groups Singing And The given method Without a control group given Singing Method. Seeing the results of research Singing Highly Effective Methods hearts improve washing capability Good And Right Hand, Singing Method Containing IF Message washing hands applied not on preschool age will impact about the lack of understanding the importance of washing hands, it is necessary to pay attention to the ability of educators for hand wash well as teach songs lying Containing Self-City Health Book. Keywords: Singing Method, Ability Handwashing